Cardiac tumors: leiomyosarcoma – a case report - Gierlak, Włodzimierz; Syska-Sumińska, Joanna; Zieliński, Piotr; Dłużniewski, Mirosław; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
We present a case report of a 60-year-old woman with a long history of leiomyosarcoma in different locations. She was admitted to the clinic due to a left ventricular tumor diagnosed in ECHO examination. The patient was qualified for radical tumor resection. The early postoperative period was complicated due to low cardiac output syndrome and bradyarrhythmia requiring temporary cardiac pacing. Optimized pharmacological therapy resulted in a gradual reduction of symptoms and a clinical improvement of congestive heart failure (NYHA III – NYHA II). Due to the radical nature of the surgery, the patient was not referred for supplementary treatment. The follow-up currently exceeds 12 months – no new metastases have been found. This case provides an example of how to diagnose and treat heart tumors.